Correction: Quantifying transient interactions between amide groups and the guanidinium cation. Issue 2 (14th December 2015) - Balos, V.; Bonn, M.; Hunger, J.
Abstract : Correction for 'Quantifying transient interactions between amide groups and the guanidinium cation' by V. Balos et al., Phys. Chem. Chem. Phys., 2015, 17, 28539–28543.